Pengembangan Materi Akidah Akhlak Berbasis Pendidikan Karakter Peduli Sosial - Yafi, Salman; Nelwati, Sasmi; Misra, Misra (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The development of moral creed material must have a contemporary concept. The decline of social concern in adolescents is a problem in today's society. This is shown by the lack of attention to social activities around the house, lack of respect for the presence of others, and lack of sensitivity to the environment. The purpose of this study is to analyze the development of Akidah Akhlak materials based on social care character education at MTsN 5 Padang City. This research is field research, meaning that it is conducted at the place in question. The approach is qualitative which allows understanding of social phenomena or human behavior through descriptive, interpretative, and in-depth analysis. The development of moral creed material in MTs is a complex process and requires deep attention to the needs of students and the environmental context. The character of social care needs to be integrated into the moral creed material considering the recent moral degradation of adolescents. The development of social care-based moral creed material is carried out in several stages. Starting from needs analysis, curriculum preparation, material development, implementation, to evaluation. Teachers of moral creed subjects can use moral creed materials that are integrated with this character education in the hope of improving the morals of their students.